دور تكنولوجيا التعليم بمراكز مصادر التعلم بمدارس الحلقة الأولى من التعليم الاساسي بمنطقة الباطنة جنوب - Shaika Ali Humaid Al Breiki; Nurkhamimi Zainuddin; Noorhayati Binti Hashim (Universiti Sains Islam Malaysia, 2024)
This quantitative study aimed to discuss the role of Educational Technology in the learning centers at the first cycle schools of basic education and to identify the obstacles that stand in the way of optimizing these centers to find suitable solutions in the form of a proposed model. It is therefore necessary to explore the views of specialists at learning resource centers on the effectiveness of learning technology. Perhaps the problem is that there is no reports to monitor the effectiveness of the requirements or development of these centers in general, and schools in the Batinah region in particular. The study sample consisted of (100) first, second and third field teacher, and (60) learning resource centers' teacher. The researcher prepared a questionnaire consisting of (88) paragraphs distributed onto 9 axes. The findings revealed that there are many obstacles facing the center, the sources of learning and the development of educational technology, through which the researcher sought to find many solutions proposed in the form of a proposed model. The researcher recommended setting up an education technology specialist for these centers and increasing the number of IT courses to make 3 weekly lessons.